Physicians' attitudes and practices regarding advanced end-of-life care planning for terminally ill patients at Chiang Mai University Hospital, Thailand - Sittisombut S. (2014)
This study examined physicians' attitudes toward advanced directives and practices for the end-of-life care at Chiang Mai University Hospital, Thailand. The data were collected from 55 physicians (24 instructors and 31 residents) using self-reported questionnaires. The majority of the participants affirmed the usefulness of the advance directive (AD) for cardiopulmonary resuscitation and respected the patients' wish for this directive, although advanced end-of-life care and resuscitation planning with the patients was limited. Mostly, the relatives were consulted regarding ADs. This study suggests that, in traditional Thai culture, physicians and families are more inclined to make decisions for the patient when they feel that it is in the patient's best interest. Further research is needed to investigate how and to what extent such attitudes can affect medical practice for end-of-life care in the context of the rapid development and consequent changes taking place in Thailand. © 2009 The Authors Journal compilation © 2009 Blackwell Publishing Asia Pty Ltd.